Why do our Theories Matter? - Rick Shearer (Journal of Open, Flexible and Distance Learning, 2021)
All too often in our practice of distance education we overlook the history of the field and our theories as we embrace new technologies or, as in the past year, when we are forced to adapt to a regional or global crisis that necessitates a temporary move to a remote learning scenario. When we set our theories aside, this approach can lead us to recreate the wheel in our pedagogical approaches, and ignores the unique pedagogy of distance education and the unique characteristics of learners studying at a distance.